The sea - Engel, Leonard 1916-1964. (New York : Time inc, 1963)
Discusses the topography of the ocean bottom, currents, waves, tides, marine life, sharks and other sea creatures dangerous to man, sea mammals, and man's methods for learning about the sea.
Includes bibliographical references and index.
Keywords: Oceanography; Marine biology; Oceanography; Marine biology